Analisis pemakaian bahan bakar biogas termurnikan pada unjuk kerja motor bakar - Sutanto, Rudy; Wardani, Kusuma; Mulyanto, Arif; Nurchayati, Nurchayati; Pandiatmi, Pandri; Zainuri, Achmad; Sinarep, Sinarep (Dinamika Teknik Mesin, 2017)
The long term purpose of this research is to obtain the high quality renewable biogas that can be used as fuel for internal combustion engines to drive an electricity generator as energy diversification efforts in the area of small sustainable islands. The specific target expected to be achieved is a method/technique for absorbing impurities contained in biogas, especially CO2 component. The study was conducted to reduce the level of CO2 in biogas using NaOH solution. The mass flow rates of biogas employed were 2, 4, 6, 8 and 10 l/min. The biogas was then tested using an engine to see the effect CO2 on the engine performance at several rotations, i.e. 1500, 2500, 3500, and 4500 rpm. The results show that the torque increases by 21.3% for biogas B2 compared to the unpurified biogas. For biogas B4, the torque increases by 19.1%. While for biogas B6, B8, and B10, the torques increase by 14.9%, 12.8%, and 8.5% respectively. For biogas B2, the SFCE decreases by 33.4%, for biogas B4, the SFCE declines of about 22.7%, while for biogas B6, the SFCE declines by 17.9%. The SFCSs also decline by 13.9% and 8.5% for biogas B8 and B10.